2014
DOI: 10.1107/s1399004714021944
|View full text |Cite
|
Sign up to set email alerts
|

Structures of an Eph receptor tyrosine kinase and its potential activation mechanism

Abstract: Eph receptor tyrosine kinases (RTKs) and their ephrin ligands play a crucial role in both physiological and pathophysiological processes, including tumourigenesis. A previous study of Eph RTKs established a regulatory role for the juxtamembrane segment (JMS) in kinase activation through the phosphorylation of two tyrosines within the JMS. Here, structures of EphA2 representing various activation states are presented. By determining the unphosphorylated inactive and phosphorylated active structures as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…No structural investigations were pursued. Recently, an EPHA2 partial‐JM‐KD construct (590–876) produced in E. coli with an N‐terminal His 6 ‐tag was crystallized in both phosphorylated form and after treatment with a dual‐specificity phosphatase PTEN . The homogeneity of the produced protein was not determined, neither was its suitability for co‐crystallization with ligands assessed.…”
Section: Introductionsupporting
confidence: 83%
“…No structural investigations were pursued. Recently, an EPHA2 partial‐JM‐KD construct (590–876) produced in E. coli with an N‐terminal His 6 ‐tag was crystallized in both phosphorylated form and after treatment with a dual‐specificity phosphatase PTEN . The homogeneity of the produced protein was not determined, neither was its suitability for co‐crystallization with ligands assessed.…”
Section: Introductionsupporting
confidence: 83%
“…Similar to c-KIT and CSF1R, we found that EPHA2 forms a potential autophosphorylation complex in a crystal structure of the kinase domain [PDB: 4PDO (23)], with a hydrogen bond between juxtamembrane region Tyr 594 and Asp 739 of the HRD motif (Fig. 1C).…”
Section: Resultsmentioning
confidence: 85%
“…Although Wei et al . (23) note that the juxtamembrane segments of each chain are ordered, point away from the kinase domain, and contact neighboring chains in the crystal, they do not mention the presence of the autophosphorylation site of these segments in the active site of the neighboring kinase protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since our previous research established the enzyme-substrate reciprocal relationship between EphA2 and PTEN14, we treated EphA2 using PTEN phosphatase to obtain an unphosphorylated autoinhibited EphA2 structure. The data collection and refinement statistics are summarized in Table S1.…”
Section: Resultsmentioning
confidence: 99%